Patients' experiences of lupus-related foot problems: a qualitative investigation. (October 2017) - Williams, A E; Blake, A; Cherry, L; Alcacer-Pitarch, B; Edwards, C J; Hopkinson, N; Vital, E M J; Teh, L S
Background: Systemic lupus erythematosus (SLE) can present with a variety of symptoms. Previous research has shown there is a high prevalence of lower limb and foot problems in patients with SLE associated with the musculoskeletal, vascular and neurological changes. Furthermore, there is a high prevalence of infections affecting the feet and a range of common skin and nail problems. However, it is not known how these foot problems impact upon people's lives. Therefore, we aimed to explore this using a qualitative approach. Method: Following ethical approval, 12 participants were recruited who had a diagnosis of SLE, current and/or past experience of foot problems and were over 18 years in age. Following consent, interviews were carried out with an interpretivist phenomenological approach to both data collection and analysis. Results: Seven themes provide insight into: foot problems and symptoms; the impact of these foot problems and symptoms on activities; disclosure and diagnosis of foot problems; treatment of foot problems and symptoms; perceived barriers to professional footcare; unanswered questions about feet and footcare; and identification of the need for professional footcare and footcare advice. Conclusion: These participants tend to "self-treat" rather than disclose that they may need professional footcare. A lack of focus upon foot health within a medical consultation is attributed to the participant's belief that it is not within the doctor's role, even though it is noted to contribute to reduced daily activity. There is a need for feet to be included as a part of patient monitoring and for foot health management to be made accessible for people with SLE.